Asuhan Kebidanan Komprehensif Pada Ny. S Umur 42 Tahun Dengan Kehamilan Resiko Tinggi Umur, Anemia Dan Kekurangan Energi Kronis (KEK) Di Puskesmas Kaliwadas Kabupaten Brebes - Rizha Yunia Lestari Dewi; Hafsah Hafsah; Sri Mulyani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
. According to WHO (2019) TB mortality rate (AKI) in the world namely 303,000 people. Maternal Mortality Rate (MMR) in ASEAN (2020), namely amounting to 235/100,000 live births. Based on data from the Ministry of Health Figures Maternal mortality (MMR) in Indonesia in 2020 was 4,627 deaths. Data Health Department (2021) MMR 62 cases. Data from Kaliwadas Community Health Center (2022) MMR 0 case. The aim of this research was to reduce maternal and infant morbidity and mortality rates in Brebes district, especially the Kaliwadas Community Health Center area. This research method is qualitative research, namely a research method carried out by exploring, describing and explaining and predicting a phenomenon that occurs on the basis of it in the field. The results of this research are after carrying out comprehensive midwifery care in Mrs. S is 42 years old with risk factors: age, anemia and CED at the Community Health Center Kaliwadas from the third trimester of pregnancy, childbirth, newborns, postpartum and family planning using Varney and midwifery approaches SOAP found gaps between theory and practice.